Variation in anatomical characteristics of bamboo, Bambusa rigida - Xing, Yan Huang; Jin, Qiu Qi; Jiu, Long Xie; Jian, Feng Hao; Bai, Dong Qin; Si, Min Chen (Universiti Kebangsaan Malaysia, 2015)
The culms of bamboo Bambusa rigida ranging from 1, 3 and 5 year old were obtained and investigated for anatomical characteristics in different ages, heights and zones in radial direction of culm wall thickness. The vascular bundles were denser and smaller at the top portion and outer zone of all age groups. No significant differences in vascular bundle frequency and size were found among the tree age groups. Metaxylem vessels did not vary significantly among ages. Fibre and parenchyma were longer in the middle portion of the height and middle zone in radial direction of culms wall. No significant differences in fibre and parenchyma length were observed in all age groups. The wall thicknesses of fibre and parenchyma were thicker in the top portion and outer zone. Furthermore, the wall thicknesses of fibre and parenchyma increased significantly from 1 to 3 year, showing that there is a maturing progress from 1 to 3 year.